Social Networks as a Learning Tool - N. Fardeeva, Irina; A. Shakirova, Indira; N. Maltseva, Elena; I. Kuzmenko, Valentina; N. Odarich, Irina (International Journal of Psychosocial Rehabilitation, 2024)
Social networks have become one of the most popular communication tools that have developed over the past decade, making them a powerful new resource for sharing information in society. Today, implementing the potential of social networking sites goes beyond leisure purposes. This article is devoted to the use of social networks in the learning environment and the impact that may have on the learning process. However, due to the random nature of social networks, there are serious concerns about the ways they can be integrated into the learning environment, as the results are varied. The effectiveness of social networks as a communication tool is already evident today, so it is quite possible that teachers should be able to create an environment for formal and informal learning that will adhere to educational guidelines [1]. Modern students are closely connected with social networks and use them in their personal lives, which makes it possible for teachers to use this as part of the educational process. The article discusses the risks of a new learning tool creation such as social networks and also explores the problems that teachers face during innovative and effective new approach application to education.